2017
DOI: 10.2147/opth.s133332
|View full text |Cite
|
Sign up to set email alerts
|

Response of eyes with age-related macular degeneration to anti-VEGF drugs and implications for therapy planning

Abstract: PurposeTo evaluate the response to and dependence on aflibercept or ranibizumab in patients with age-related macular degeneration (AMD).MethodsWe retrospectively reviewed AMD patients who received induction therapy with aflibercept or ranibizumab for the following parameters: whether complete resolution of the retinal fluid (“good response”) was achieved and whether recurrence was observed within 3 months (“dependent”) after the induction treatment. With aflibercept treatment, treatment-naïve eyes with a good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…We reported that the evaluation of the response and dependence on anti-VEGF agents in AMD was useful and practical in managing protocols to obtain a good VA 19. We had also applied the PrONTO study procedures20 for patients treated with ranibizumab as retreatment criteria in the LAPTOP study, and after switching to aflibercept, the patients were retreated when any fluid was observed in OCT. That may also explain why the achievement rate of dry macula also increased at 5years in the ranibizumab group.…”
Section: Discussionmentioning
confidence: 99%
“…We reported that the evaluation of the response and dependence on anti-VEGF agents in AMD was useful and practical in managing protocols to obtain a good VA 19. We had also applied the PrONTO study procedures20 for patients treated with ranibizumab as retreatment criteria in the LAPTOP study, and after switching to aflibercept, the patients were retreated when any fluid was observed in OCT. That may also explain why the achievement rate of dry macula also increased at 5years in the ranibizumab group.…”
Section: Discussionmentioning
confidence: 99%
“…Minami et al 9 used an aflibercept regimen of 3 consecutive monthly injections followed by treatment at 2-month intervals in naive nvAMD eyes with good baseline visual acuity and reported a significant increase in visual acuity from month 2, as well as “dry macula” (no exudative findings on OCT) in 80% of eyes after the 3 loading doses and in 66% and 71% at months 6 and 12, respectively. In a similar study, Miyamoto et al 10 reported anatomical success rates of 37%, 62%, and 81% at months 3, 6, and 12, respectively, in eyes with naive AMD given aflibercept at 2-month intervals following a 3-month loading dose. Looking at studies conducted in our country, Erden et al 11 evaluated the anatomic and functional efficacy of aflibercept and ranibizumab in nvAMD and observed statistically significant positive changes at the end of 12 months with the pro re nata protocol in the aflibercept arm of the study.…”
Section: Discussionmentioning
confidence: 82%
“… 4 , 16 , 17 When our study results were analyzed, it was observed that the presence of PCV at diagnosis was not associated with anatomic response to IVA treatment in group 1 or 2 (p>0.999, p=0.801, respectively). Miyamoto et al 10 also reported that the presence of PCV did not affect anatomic response to IVA in their study of naive eyes with nvAMD, nearly half of which had PCV, while Ijiri and Sugiyama 18 reported an anatomic success rate of 97% in naive eyes with PCV after 3 consecutive IVA injections.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…AMD-associated pathways and factors that stimulate CNV remain to be fully elucidated. However, vascular endothelial growth factor A (VEGF-A), a cytokine that promotes angiogenesis and vascular permeability, is one of the most important factors that promotes neovascularization (6). Active forms of VEGF-A have been identified in CNV (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%